Comparison of Maternal Age Risk Factors forLow Birth Weight (LBW): A Literature Review - Gede Arif Danu Arta; Ni Putu Dewi Sri Wahyuni; Made Suadnyani Pasek (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Introduction: Low Birth Weight (LBW) remains a key indicator of perinatal healthand continues to be a significant concern due to its association with increasedneonatal morbidity and mortality. Differences in maternal age, particularlyadolescent and advanced maternal age groups, are believed to contribute to LBWthrough distinct biological and clinical mechanisms. This review aims to compareLBW risk across maternal age groups and to explore the underlying biologicalpathways and contributing factors.Method: Literature searches were conducted through Google Scholar, PubMed,and ScienceDirect using keyword combinations related to LBW and maternalage. Article selection followed inclusion criteria of publications within the last tenyears, written in English or Indonesian, and employing quantitative study designs.Eligible studies were analyzed descriptively using a PICO framework to compareLBW risk among different maternal age categories.Discussion: The review indicates that adolescents face a higher likelihood ofLBW due to biological immaturity, nutritional competition between maternal andfetal growth, and psychosocial factors that may impair pregnancy health. Incontrast, advanced maternal age is primarily associated with LBW throughincreased obstetric complications, such as hypertension and impaired placentalperfusion, which restrict fetal growth. Differences in findings across studies areinfluenced by variations in confounder control, suggesting that observed risksreflect not only age itself but also accompanying health conditions.Conclusion: Both younger and older maternal age groups contribute to LBWthrough differing mechanisms. Effective prevention requires antenatal carestrategies tailored to the specific risk profiles of each age group to reduce thelikelihood of LBW.